SARS-CoV-2 placentitis - report of two cases and review of the literature - Daumová, Magdaléna; Hadravská, Šárka; Peteříková Straková, Andrea; Vaněček, Tomáš; Matas, Martin; Korečko, Vladimír (Ceska gynekologie, 2022)
Covid-19 disease caused by severe acute respiratory syndrome 2 coronavirus (SARS-CoV-2) continues to be a global public health problem. Since the pandemic outbreak in early 2020, a number of cases have been reported in pregnant women whose infection has led to severe complications including preterm birth, miscarriage, intrauterine growth restriction or intrauterine fetal demise. The results of the current studies suggest that the transplacental transmission of infection from mother to fetus is a rare event and that the complications listed above are more likely due to damage of placental tissue. In this article, we describe two cases of SARS-CoV-2 placentitis with special consideration to the morphology and differential dia-gnosis of this newly defined entity.
Keywords: COVID-19; Placenta; těhotenství; Humans; placenta; Pregnancy Complications, Infectious; placentitis; předčasný porod; Infant, Newborn; novorozenec; ženské pohlaví; Premature Birth; lidé; infekční komplikace v těhotenství; SARS-CoV-2; Pregnancy; vertikální přenos infekce; histiocytic intervillositis; Infectious Disease Transmission, Vertical; Female